Entre a censura e a desordem fecunda: a constituição do Teatro Oficina (1961-1970) - Valentini, Daniel Martins (2011)
This work aims to develop a reflection about the censorship of Teatro Oficina in 1960s, watching as the action of the repressive apparatus with the group, before and after the 1964 coup, seeking to understand the changes that occurred with the hardening of the dictatorial regime. In this quest, we realized that the researches on the Oficina focused mainly on memory of Zé Celso, while other group members had their narratives ignored. We feel, therefore, the need to also work with the other historical actors narratives